Strengthening Students' Arabic Writing Skills Through Insya’ Muwajjah in Higher Education - Zulaeha Zulaeha; Musdalifah Musdalifah (AL-ISHLAH: Jurnal Pendidikan, 2022)
Writing is an activity to actualize one's abilities and scientific specialization to the public because, from writing, one's scientific quality and discipline can be known. Writing is also a means of communication that is not limited by time and place. Writing skills need to be honed to produce relevant and valuable works. This study aims to analyze and understand the strengthening of students' writing skills through insya’ muwajjah in learning Arabic at the State Islamic Institute of Kendari. The research method uses a qualitative case study approach. Data were obtained from interviews with several faculty leaders, heads of study programs, lecturers, and students. The data analysis technique is carried out through data collection, presentation, and reduction, concluding. The results showed that; Arabic learning activities through the insya’ muwajjah approach to strengthening students' writing skills are carried out through; Brainstorming (early understanding), guided training (intensive guidance), creating a literacy climate, providing facilities and infrastructure. This study implies that lecturers can provide motivation and enthusiasm to apply writing skills supported by appropriate methods and applications to produce quality programs.